Eksplorasi Orientasi Pemasaran Sekolah dalam Meningkatkan Jumlah Siswa Baru di Sakinah Boarding School - Dendang Karnila; Kimiatis Sa’adah; Hendy Rijalul Vikri; Deni Setiadi; Ismiyati (MGMP PAI SMP BINTAN, 2025)
This study aims to explore the market orientation and marketing strategies applied by Islamic schools in an effort to increase the number of new students. Data was obtained using a qualitative approach with an exploratory case study design through observation, documentation and in-depth interviews with 15 resource persons consisting of foundation administrators, school leaders, marketing division, public relations and publications as well as teachers. The results showed that the market orientation of Sakinah Boarding School (SBS) is very customer-oriented, proficient in inter-functional coordination and the culture developed in the school is very market-oriented. The marketing strategy implemented covers various aspects, such as the use of social media, strengthening relationships with the community, promotional programs, and the quality of educational services. However, the school has a limited budget for marketing and the lack of understanding of teachers and employees about the importance of marketing orientation in education. This research can be used as a guide for integrated Islamic schools with the Boarding School concept in determining market orientation and marketing strategies and also taken into consideration for further research.